Penatalaksanaan Fisioterapi Pada Kasus Ischialgia Akibat Hernia Nucleus Pulposus (Hnp) Vl4-L5, L5-S1 Di Rsud Dr. Harjono Ponorogo - Kurniawati, Ika Rizki; , Maskun Pudjianto, SMPh., M.Kes (2016)
Background: Hernia Nucleus Pulposus (HNP) is a condition nucleus pulposus come out from disc through annulus fibrosus torn come out to back or dorsal pressed spinalis nerve so, that may be cause pain disruption. Ischialgia (or sciatica), a condition where ischiadicus nerve in along of lower limb occur irritation, is the example of nerve root pain which common occur. Ischialgia (sciatica) defined of pain radiating from back until buttock and lower limb. At this condition needed physiotheraphy intervention such as Short Wave Diathermy (SWD), Transcutaneous Electrical Nerve Stimulation (TENS), Mc.Kenzie Exercise and Core Stability Exercise. Purpose: to know benefit physiotheraphy management to handled problems in ischialgia condition caused by HNP. Result: after treatment of 6 times the result obtained any changes in the intensity of pain in quiet from T0 = 4 to T6 = 1, compression pain T0 = 7 to T6 = 3, movement pain when trunk flexion T0 = 7 to T6 = 3, movement pain when hip flexion sinistra T0 = 6 to T6 = 2. There are increase of muscle strength trunk fleksor from T0 = 2 to T6 = 3, trunk extensor T0 = 3 to T6 = 4, lateral fleksor dextra T0 = 3 to T6 = 4, lateral fleksor sinistra T0 = 3 to T6 = 4, fleksor hip sinistra T0 = 2 to T6 = 3, not found increase in extensor hip sinistra from T0 = 4 to T6 = 4. At LGS examination showed the result obtained there are increase of LGS when trunk flexion T0 = 2 cm to T6 = 4 cm, trunk extension T0 = 4,5 cm to T6 = 5 cm, side flexion to sinistra T0 = 6 cm to T6 = 6,5 cm, side flexion to dextra T0 = 6 cm to T6 = 6,5 cm, there are increase of LGS hip sinistra in flexion - extention from T0 : S = 20o - 0o - 40o to T6 = 25o - 0o - 50o. At functional ability examination with Oswestri showed that functional ability value obtained increase from T0 = 48 % to T6 = 42 % but in dependence level is decided in serve disability level. Conclusion: giving intervention like SWD, TENS, Mc.Kenzie Exercise dan Core Stability Exercise can decrease of pain, increase of LGS, and also increase functional ability.